Marketing strategy development and market segmentation analysis of PT. Wijaya Karya on government policies in the building EPC champion program - Arga Bima; Atik Aprianingsih (Universitas Mercu Buana Yogyakarta, 2022)
The Indonesian government's efforts to synergize state-owned enterprises continue to be intensifying. The Ministry of State-Owned Enterprises continues to streamline and improve the portfolio of the number of SOEs through corporate restructuring with a holding system, mergers, and acquisitions. As an initial step towards creating an infrastructure SOES holding, the Ministry of SOES launched a